Improving Learning Outcomes of Underwear Passing In Volleyball Through The Use of Plastic Ball Media For Grade IV Students of SD Inpres Mare (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the improvement of learning outcomes of underhand passing in volleyball through the use of plastic balls for fourth-grade students of SD Inpres Mare. This study uses a Classroom Action Research (CAR) design implemented in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of the study were all 28 fourth-grade students of SD Inpres Mare using a total sampling technique. The independent variable in this study was the use of plastic balls, while the dependent variable was the learning outcomes of underhand passing. Data were collected through skills tests and observations, then analyzed using quantitative descriptive analysis techniques with percentages. The results showed a significant improvement in students' underhand passing learning outcomes. In cycle I, learning completeness reached 64% with an average score of 74. After improvements were made in cycle II, learning completeness increased to 86% with an average score of 81. This improvement was seen in all three learning domains: cognitive increased from 61% to 89%, affective from 64% to 86%, and psychomotor from 68% to 82%. The conclusion of this study shows that the use of plastic ball media is effective in improving the learning outcomes of underhand passing in grade IV students of SD Inpres Mare.